Persamaan di Depan Hukum dalam Konteks Pengupahan dan Perekrutan Pekerja - Rony Andre Christian Naldo; Christian Orchard Perangin-angin; Mesdiana Purba (Jurnal Ilmiah Penegakan Hukum, 2019)
PT. PN III is inseparable from workers. In work relations, of course equality must be applied before the law. In fact, there is discrimination in the context of wages for male and female workers. In addition, in the context of recruitment of workers, discrimination also occurs, which prioritizes the recruitment of male workers rather than female workers. This study discusses the similarities before the law in the context of wages and recruitment of workers at PT. PN III. In connection with this, this study specifically discusses the causes of not applying equality before the law in the context of wages for female workers at PT. PN III, and the cause of prioritization is the recruitment of male workers rather than female workers at PT. PN III. This study uses a type of normative legal research, using normative juridical methods, and is descriptive analytical. As a conclusion, the cause for not applying equality before the law in the context of wages for female workers at PT. PN III is a result of the provisions of Article 44 paragraph (1) and (4) Collective Labor Agreement for the 2016-2017 Period Between PT. PN III With SPBUN PT. PN III. The reason for prioritizing the recruitment of male workers is that female workers at PT. PN III is because male workers work more effectively than female workers.